RESPON TIGA VARIETAS TANAMAN KACANG HIJAU (Vigna radiata L.) TERHADAP PEMBERIAN LIMBAH PADAT (Sludge) PABRIK KELAPA SAWIT - Rachmat Alexander; Adiwirman Adiwirman; Idwar Idwar (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2020)
Mung beans are legumes that known and cultivated in Indonesia. This plant is an important commodity. Utilization of oil palm processing plant sludge is still not optimal, therefore sludge can be utilized as an alternative supply of nutrients for the development of green bean plants. PKS sludge is the waste from the byproduct of the processing of fresh fruit bunches (FFB) in the form of solid objects that sink at the bottom of the sedimentation plant of a palm oil mill into crude palm oil or Crude Palm Oil (CPO). The study was conducted at the Technical Implementation Unit (UPT) Experimental Garden of the Faculty of Agriculture, University of Riau from August to October 2018. The research was an experiment in the pattern of a 4x3 factorial using a split plot design. As the main plot, PKS sludge solid waste consists of 4 levels (0, 8, 16, and 24 tons.ha-1), as subplots namely three varieties of green bean plants consist (varieties Vima-1, Kutilang and Vima-3) , each repeated 3 times. The results showed there were variations among varieties of green beans, which were observed in which Vima-1 variety gave better results for the age of emergence of flowers, age of harvest, and weight of 100 seeds. Varieties of Kutilang on the parameters of percentage of pith pods and Vima-3 varieties on parameters of plant height, number of branches, number of seeds per pod and weight of seeds per plot. Of the three varieties tested, Vima-3 produced the highest plant height of 65.12 cm and yieldof 493.74 gr.m-2. Keywords: Green beans, varieties, sludge